Avaliação dos mecanismos de incentivo no repasse da cota parte do ICMS considerando critérios de saúde e saneamento - Campos, Felipe Rocha (2021)
The sanitation and health conditions of a region are related to the development of society, by reducing the transmission of diseases and, therefore, improving health conditions and the formation of human capital. The implementation of incentive policies based on discretionary indicators can be an efficient alternative to make it possible to obtain better indicators in the states that implement such criteria. In this sense, item IV of Article 158 of the Federal Constitution of 1988 provides for the collection of the state ICMS tax and the distribution of the municipal share, in accordance with the provisions of state law. Thus, this paper seeks to analyze the impact of implementing an incentive mechanism based on state laws that use health and sanitation criteria to distribute the ICMS quota. For this, data from the IBGE demographic censuses are used to build the strategy for identifying and estimating the difference-in difference models, without and with PSM, to assess the impact of state laws. According to the results, Pernambuco and Tocantins have better results on health indicators, although they have not directly impacted the sanitation sector. In the case of the states of Ceará and Piauí, there is an impact on the basic sanitation sector, without consistent results for the health sector, as these vary according to each model under consideration. Therefore, the laws implemented in these states were effective in obtaining better indicators in the analyzed sectors. While for the estimations for the states of Espírito Santo and Amapá the expected results with the policy are not obtained. Therefore, the simple implementation of the ICMS transfer law with sanitation and health criteria is not enough to allow a significant improvement in the sector, but if these are well designed and well implemented, it is possible that it will result in a significant evolution of the analyzed indicators.